All‐in‐One Photoacoustic Theranostics Using Multi‐Functional Nanoparticles. (27th October 2021) - Li, Tingting; Guo, Heng; Liu, Ye; Qi, Weizhi; Wu, Changfeng; Xi, Lei
Abstract: Both treatment and postoperative evaluation of cancer play vital roles in improving the survival rate of patients. However, existing cancer therapies face multiple challenges of low drug delivery efficiency, separation of treatment and evaluation, and lack of noninvasive, routine and cost‐efficient postoperative monitoring methods. To overcome these issues, an all‐in‐one anti‐cancer strategy is proposed by using the combination of the photoacoustic (PA) effect and polymer nanoparticles. This strategy shows enhanced nanoparticles delivery, significant tumor ablation, and the capability of non‐invasive and longitudinal postoperative evaluation. Near‐infrared (NIR) excited photoacoustic radiation force (PAF) based on the high optical absorption nanoparticles opens the vascular barrier, accumulates the nanoparticles inside the tumor, and enables visualization of real‐time nanoparticles distribution. Instead of conventional thermal therapy by using a continuous wave laser, the NIR pulsed laser coupled with PAF offers thermal therapy with further positive accumulation of nanoparticles, and significantly improves the treatment efficiency in return. In addition, the endogenous hemoglobin enables PA imaging to evaluate the efficacy of tumor therapy and monitor the progress of postoperative tumors in vivo through structural and functional parameters of the vascular network. This study presents a new opportunity for formulation of personalized and accurate tumor therapy, and timely feedback of therapeutic effect. Abstract : In this study, the proposed all‐in‐one photoacoustic theranostics strategy using the combination of the photoacoustic effect and polymer nanoparticles can provide promoted nanoparticles delivery, significant tumor ablation, and non‐invasive, longitudinal postoperative evaluation. It is demonstrated that the pulsed lasers coupled with multi‐functional nanoparticles offers a thermal therapy against tumors and the feedback of therapeutic effect in tumor‐bearing mice.